Технология проектов на уроках математики как одна из эффективных технологий достижения планируемых результатов - Искакова, У.А. (My University, 2016)
The article describestechnologyprojects, the stages of a project, and is marked with the assessment criteria. An exampleof thepractice is the substantiationthat the use oftechnologyprojectscan achievethe expected results.
Keywords: projectdesign activity; stages of project implementation; effectiveness; criteria for evaluatingthe result